EFEKTIFITAS PROMOSI KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP WANITA TERHADAP IVA TEST DI WILAYAH PUSKESMAS SUKOHARJO 1 TAHUN 2016 - Fridayanti, Warni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Cervical cancer is a disease with the highest prevalence in women in the world that causes death. Nearly 80% of cervical cancer cases are in developing countries. In Indonesia, 80% - 90% of patients with cervical cancer are usually difficult to cure because they come to the health care with more than 70% are in advanced stage. Lack of knowledge and awareness in women about early detection of cervical cancer is one of the main factors. Health promotion is needed to improve the women’s knowledge to increase the women’s awareness about early detection of cervical cancer. Quasi-experimental study with pretest-posttest randomize design was used. Sample in this study 96 respondents. The study was conducted in October 2016. Data analysis included univariate, bivariate test analisisis wilcoxon and mann Whitney. Results showed significant differences between before and after the health promotion using leaflets in knowledge (0.002), attitude (0.003), and there were also significant differences between before and after health promotion through motivation from community leaders in knowledge (0.000), attitude (0.000). There were also significant differences between the health promotion using leaflets and the health promotion through motivation from community leaders in knowledge (0.000) and attitude (0.002). Keywords: Health Promotion; Knowledge; Attitude; IVA test